Return to sport in elite gymnastics: Unprecedented training interruptions provide lessons for the future - Casey, E.; Bonanno, J.; Cheng, J.; Abutalib, Z.; Kranz, K.; Kruse, D.; Thomas, C.; Faustin, M. (PM&R, 2023)
Introduction: Year-round training is standard for elite gymnasts in the United States, but the coronavirus disease 2019 (COVID-19) pandemic led to unprecedented training interruptions. The effect of these training disruptions is unknown. Objective: This study aimed to describe and compare training interruptions in elite gymnasts before and during the pandemic, the time it took to return to the prior level of gymnastics training, the development of injuries during return to gymnastics training, and gymnast-reported difficulty in and nervousness about returning to prior level of gymnastics training. Design: Retrospective study. Setting: Anonymous online surveys distributed to elite gymnasts in the United States. Participants: A total of 184 current elite gymnasts who completed the surveys were included. This represented an overall response rate of 52.3% (184/352). Interventions: None. Main Outcome Measures: Information was collected about training interruptions and time, nervousness, difficulty, and injury during return to gymnastics. Results: Gymnasts reported significantly longer training interruptions due to COVID-19 than before the pandemic (8.7 ± 4.4 vs. 4.4 ± 7.9 weeks, p < .001), but duration of return to prior gymnastics level was similar (4.6 ± 2.7 vs. 3.7 ± 4.8 weeks, p = .106). Of the 137 gymnasts who had returned to training by the time of the survey, 46 (33.6%) reported an injury during their return to gymnastics. A high degree of nervousness to return to gymnastics was significantly associated with greater risks of injury upon return (risk ratio [RR] 2.7, 95% confidence interval [CI]: 1.6-4.7; p < .001) and difficulty returning to prior level (RR 3.4, 95% CI: 1.7-6.6; p < .001). Conclusion: Pandemic-related training interruption was significantly greater in duration than prior interruptions, but time required for return to gymnastics was similar. Gymnasts may be at increased risk of injury during return to gymnastics if experiencing nervousness about returning following a break in training. These findings provide guidance for gymnasts' return from training interruptions and may refute the long-held belief that gymnasts should not take time away from training due to fear of injury or difficulty regaining skills.